SEMANTIC SHIFT IN THE ENGLISH - INDONESIAN TRANSLATION OF DESSEN’S WHAT HAPPENED TO GOODBYE - Husseni, Shadam; Hartono, Rudi (English Education Journal, 2018)
This study focused on the semantic shift in the English – Indonesian Translation of Dessen's What Happened to Goodbye. The main purposes of the study was to explain shift or transposition is termed as shift is a translation procedure involving a change in the grammar from source language to target language. Translation shift is termed involves replacing one word class with other without changing the meaning of the message. This study carried out in order to find out the kinds of semantic shift are found in English – Indonesian Dessen’s What Happened to Goodbye. This study assess the quality of English – Indonesian translation of semantic shift in Dessen’s What Happened to Goodbye. This research was a descriptive qualitative research. The object of this study is English - Indonesian pun translation of Dessen’s What Happened to Goodbye. The quality assessment of this study is obtained from the respondents. The respondents are divided into two, they are expert rates (the lecturers) and target readers (the teenager). In the analysis of semantic shift in the What Happened to Goodbye, from the results of analysis, the writer found the first type of shift (The change from Singular to Plural and the position of Adjective); the second type of shift (in SL Grammatical Structure does not exist in TL); the third type of shift (the one where literal translation is grammatically possible but may not accord with natural usage in the TL) and the fourth type of shift (the replacement of a virtual lexical gap by a grammatical structure). The analysis on the translation quality shows that 108 translations (23%) are considered as accurate, and 287 translations (77%) are considered as less accurate. In clarity level, 176 translations are belong to clear (47, 7%), and 219 translations are belong to unclear (52, 3%). Naturalness level shows that 246 translations (54, 7%) are categorized as very natural, and 149 translations (45, 3%) are categorized as sufficient natural.